Stabilization of Clayey Soil with Alkali-activated Hybrid Slag/Cement - Yıldırım, Eray; Bol, Ertan; Avcı, Eyübhan; Özocak, Aşkın (Periodica Polytechnica Civil Engineering, 2024)
This study investigates the stabilization performance of clayey soil treated with alkali-activated hybrid slag/cement. Sodium silicate (SS) and sodium hydroxide (SH) are used as alkali activators, whereas ground blast furnace slag (GGBS) and ordinary Portland cement (OPC) are used as sources of aluminosilicate. A total of 27 different types of mixtures are used for stabilization. Unconfined compressive strength (UCS) of untreated clay and stabilized soils are performed at immediately, 3-, 7-, 28-, and 90 days curing times under air-dried and wet-cured conditions. In addition, 90-d volume and mass changes in the samples are measured. Stabilized samples with an SS/SH ratio of 1 under air-dried conditions reveal moistening at early curing ages (≤28 days); afterward, sodium carbonate crystals appear in these samples at longer curing ages. Geopolymer-treated clayey soil exhibits lower volumetric and mass changes compared with OPC. Most of the stabilized clayey soil with alkali-activated hybrid slag/cement exhibits higher strength compared with OPC under air-dried and wet-cured conditions.